Next-generation sequencing yields the complete mitogenome of the stored nut moth, Paralipsa gularis Zeller (Lepidoptera: Pyralidae). Issue 9 (2nd September 2021) - Guo, Ping; Yu, Hong; Xu, Jin; Li, Yong-He
Abstract: The stored nut moth, Paralipsa gularis Zeller 1877 (Lepidoptera: Pyralidae), is a pest of stored products. In this study, the whole mitogenome of P. gularis was identified for the first time by using the next-generation sequencing (NGS) systems. The entire genome is 15, 280 bp in length (ACCN: MW135332) consisting of 13 protein-coding genes (PCGs), two ribosomal RNA genes, 22 transfer RNA genes, and an A + T-rich region. Phylogenetic analysis using 13 PCGs of 20 species derived from six moth superfamilies showed that Pyralidae moths are monophyletic. This study can provide essential DNA molecular data for further phylogenetic and evolutionary analysis for Pyralidae family of Lepidoptera order.